Struktur dan Ciri Kebahasaan Teks Eksposisi Karya Siswa Kelas X SMA Pertiwi 1 Padang - Harahap, Anri Ahmadi; Amir, Amril (Lembaga Yasin AlSys, 2023)
The research was conducted with the aim of describing the structure and linguistic characteristics of exposition texts by class X SMA Pertiwi 1 Padang. This research is a qualitative type with a descriptive method. The data and data sources in this study are the structure and linguistic characteristics of the exposition texts of 36 students' works. The researcher is the instrument of this research. The data collection technique applied is documentation. Data analysis was carried out by identifying general data, identifying data based on theory, analyzing data, recording data that had been analyzed, and concluding. The findings in this study are first, class X SMA Pertiwi 1 Padang is classified as good in the use of exposition text. This is reviewed based on the completeness and accuracy of the use of theses, arguments, and restatements. Even so, there are still some uses of thesis, argumentation, and restatement that are not in accordance with the theory. Second, students have used the four linguistic characteristics, namely pronouns, nouns, verbs, and conjunctions.